Integrating TPACK in Extensive Listening: Teachers' Experiences - Dewi Kurniawati; Nunun Indrasari; Fithrah Auliya Ansar (CV FOUNDAE, 2023)
In March 2020 and the global outbreak of the coronavirus prompted the government to adjust its policies including the closure of educational institutions and swiftly shift to online learning. The aim of the research study was to describe the experiences of three English-language lecturers who taught listening during the Covid-19 Pandemic. It examines the challenges faced, including the shift to distance education, the preparation of teaching materials, and the navigation of unexpected obstacles. This research used collaborative auto-ethnography (CAE) as a qualitative study. This method involves the collaboration between the first, second, and third authors to gain understanding and insight into their shared experience. The data collection process was conducted in early 2021. After we taught extensive listening in the 3rd semester of the academic year 2020-2021. For collecting the data we used the story of our experience in a narrative inquiry, photo voice, and semi-structured interview that was analyzed using a thematic analysis. The fings of this study, from the experiences of the three authors as lecturers indicate that the epidemic situation is not a barrier to contributing positively to the world of education. One of the positive effects is that it can increase the creativity of teachers or lecturers in developing teaching materials and using TPACK and also help students evaluate concepts and theories more critically. This study also reveals that, despite experiencing problems such as unstable internet signals in their respective areas, teachers and lecturers are able to adapt to both academic and non-academic environments.